Assessment of the aerosol optics component of the coupled WRF–CMAQ model using CARES field campaign data and a single column model. (August 2015) - Gan, Chuen Meei; Binkowski, Francis; Pleim, Jonathan; Xing, Jia; Wong, David; Mathur, Rohit; Gilliam, Robert
Abstract: The Carbonaceous Aerosols and Radiative Effects Study (CARES), a field campaign held in central California in June 2010, provides a unique opportunity to assess the aerosol optics modeling component of the two-way coupled Weather Research and Forecasting (WRF) – Community Multiscale Air Quality (CMAQ) model. This campaign included comprehensive measurements of aerosol composition and optical properties at two ground sites and aloft from instrumentation on-board two aircraft. A single column model (SCM) was developed to evaluate the accuracy and consistency of the coupled model using both observation and model information. Two cases (June 14 and 24, 2010) are examined in this study. The results show that though the coupled WRF–CMAQ estimates of aerosol extinction were underestimated relative to these measurements, when measured concentrations and characteristics of ambient aerosols were used as input to constrain the SCM calculations, the estimated extinction profiles agreed well with aircraft observations. One of the possible causes of the WRF–CMAQ extinction errors is that the simulated sea-salt (SS) in the accumulation mode in WRF–CMAQ is very low in both cases while the observations indicate a considerable amount of SS. Also, a significant amount of organic carbon (OC) is present in the measurement. However, in the current WRF–CMAQ model all OC is considered to be insoluble whereas most secondary organic aerosol is water soluble. In addition, the model does not consider external mixing and hygroscopic effects of water soluble OC which can impact the extinction calculations. In conclusion, the constrained SCM results indicate that the scattering portion of the aerosol optics calculations is working well, although the absorption calculation could not be effectively evaluated. However, a few factors such as greatly underestimated accumulation mode SS, misrepresentation of water soluble OC, and incomplete mixing state representation in the full coupled model simulation are possible causes of the underestimated extinction. Improved SS emission modeling and revisions to more fully account for OC in the optical calculations are being pursued. More sensitivity tests related to the factors mentioned previously are needed for future optical properties development.